1998
DOI: 10.1101/gad.12.12.1825
|View full text |Cite
|
Sign up to set email alerts
|

The ErbB2 and ErbB3 receptors and their ligand, neuregulin-1, are essential for development of the sympathetic nervous system

Abstract: Neuregulins (NDF, heregulin, GGF ARIA, or SMDF) are EGF-like growth and differentiation factors that signal through tyrosine kinase receptors of the ErbB family. Here, we report a novel phenotype in mice with targeted mutations in the erbB2, erbB3, or neuregulin-1 genes. These three mutations cause a severe hypoplasia of the primary sympathetic ganglion chain. We provide evidence that migration of neural crest cells to the mesenchyme lateral of the dorsal aorta, in which they differentiate into sympathetic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
242
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 304 publications
(253 citation statements)
references
References 56 publications
10
242
1
Order By: Relevance
“…The impaired glial cell migration in these mutants indicates a direct function in migration. This interpretation is supported by the finding that mutations in the neuregulin-ErbB signalling system lead to changes in neural crest migration in mice (Britsch et al, 1998) and in directed Schwann cell migration in zebrafish (Lyons et al, 2005). However, an earlier function in fate specification and/or proliferation that could in turn be a prerequisite for migration cannot be completely ruled out.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The impaired glial cell migration in these mutants indicates a direct function in migration. This interpretation is supported by the finding that mutations in the neuregulin-ErbB signalling system lead to changes in neural crest migration in mice (Britsch et al, 1998) and in directed Schwann cell migration in zebrafish (Lyons et al, 2005). However, an earlier function in fate specification and/or proliferation that could in turn be a prerequisite for migration cannot be completely ruled out.…”
Section: Introductionsupporting
confidence: 68%
“…The development of peripheral nerve tissue results from a series of coordinated interactions between neurons and Schwann cells (Jessen and Mirsky, 2005). Targeted mutagenesis of different components of the ErbBsignalling complex has demonstrated its importance for Schwann cell development (Britsch et al, 1998;Garratt et al, 2000;Michailov et al, 2004;Riethmacher et al, 1997;Taveggia et al, 2005). Those experiments revealed that, later in development, mutant embryos exhibit a total loss of Schwann cells along their peripheral axons, whereas pre-migratory Schwann cells are present near to the dorsal root ganglia but fail to migrate along the axons.…”
Section: Introductionmentioning
confidence: 99%
“…Conditional deletion of ErbB2 in the ventricular myocardium of mice leads to postnatal dilated cardiomyopathy and death [121,122]. In addition, mice deficient in ErbB2 show defects in cranial sensory ganglia likely due to defects in cranial neural crest [119,123]. ErbB2 plays a role in the terminal differentiation of oligodendrocyte precursors to mature oligodendrocytes in the spinal cord [124] as well as in the myelination of peripheral nerves by Schwann cells [125][126][127].…”
Section: Erbb Members In Mammalian Developmentmentioning
confidence: 99%
“…[286][287][288] Failure of migration of progenitor cells from neural crest was similarly observed in Erbb3, Erbb2 and Nrg knockout mice, implying a role for Nrg to Erbb3/Erbb2 signaling. 285,289,290 ERBB3 also has an essential role in development of the human nervous system: lethal congenital contractural syndrome 2, an autosomal recessive trait associated with atrophy of the anterior horn of the spinal cord, is caused by aberrant splicing of ERBB3. 291 In adult rodent brain Erbb3 mRNA, with prominence mainly in white matter, has an expression pattern different from that of Erbb4.…”
Section: Hematopoietic Neoplasmsmentioning
confidence: 99%